(untitled) (Research, Society and Development, 2022)
The nature of this article is qualitative. The objective was to discuss in an exploratory way the identity characteristics and the environmental practices of the Pomeranians in the municipality of Marechal Cândido Rondon-PR. The methodology consists of the use of Logical Matrix and qualitative data analysis, with the help of the MAXQDA tool. A questionnaire composed of twenty open and closed questions was individually applied to nine Pomeranians who live in the municipality in question. The results revealed similar occurrences especially in relation to language competence, where the majority of the interviewees spoke Pomeranian, Portuguese and German (Hunsrück). Furthermore, it is noticeable that in relation to agriculture, the interviewees demonstrate a high degree of knowledge, in a socioeconomic logic of subsistence and achievement of life purposes. The struggle for their identity culture is kept alive, based on cultural rites, community, generational, and religious relations. According to the sample of interviewees, it was found that the Pomeranians of Rondon have a specific way of living and acting environmentally, however, they tend to suffer influences of the agricultural technological package.